Health‐related quality of life after post‐haemorrhagic hydrocephalus in children born preterm. (6th September 2018) - Gigi, Moran; Roth, Jonathan; Eshel, Rina; Constantini, Shlomi; Bassan, Haim
Abstract : Aim: To determine the health‐related quality of life (HRQoL) of children born preterm (gestational age <32wks) after post‐haemorrhagic hydrocephalus requiring shunt (PHH‐S), and to examine the impact of perinatal and neurological morbidity on their QoL. Method: Forty infants (18 females, 22 males; aged 2y 2mo–8y 4.5mo) born preterm with PHH‐S were matched for gestational age, birthweight, and sex with infants born preterm with normal cranial ultrasonography. Pediatric QoL Inventory parent‐proxy report was administered at a mean age of 5 years 8 months. Results: Children with PHH‐S exhibited significantly lower mean HRQoL compared with controls in motor (36 [SD 34.9] vs 96.2 [SD 6.6]), emotional (59.8 [SD 26.7] vs 80.6 [SD 18.8]), social (55.6 [SD 29.7] vs 89.6 [SD 16.6]), and school (40.5 [SD 22.9] vs 89.7 [SD 15.2]) domains ( p <0.001). Multivariate regression incorporating neonatal risk factors revealed an independent effect of parenchymal brain involvement ( β =−0.6, p <0.01) and neonatal seizures ( β =−0.2, p <0.02) on total HRQoL. Low HRQoL of children with PHH‐S was associated with neurodevelopmental morbidities: cerebral palsy (CP), epilepsy, vision and feeding problems, low cognitive, personal–social, and adaptive scores ( p <0.05). Multivariate analysis indicated an independent contribution from severe CP ( β =−0.4, p <0.001) and low personal–social score ( β =0.5, p <0.001). Interpretation: Children born preterm after PHH‐S exhibit significantly lower HRQoL scores compared with preterm born peers. HRQoL is associated with neonatal cerebral complications and neurodevelopmental morbidities. What this paper adds: Children born preterm, after post‐haemorrhagic hydrocephalus requiring shunt, have low health‐related quality of life (HRQoL). A low HRQoL is associated with parenchymal brain involvement and with neurological morbidity. Severe cerebral palsy and low personal–social developmental scores have independent contributions to HRQoL. What this paper adds: Children born preterm, after post‐haemorrhagic hydrocephalus requiring shunt, have low health‐related quality of life (HRQoL). A low HRQoL is associated with parenchymal brain involvement and with neurological morbidity. Severe cerebral palsy and low personal–social developmental scores have independent contributions to HRQoL. This article is commented on by Whitelaw on page288 of this issue. This article's abstract has been translated into Spanish and Portuguese. Follow the links from theabstract to view the translations.